The Effectiveness of Papaya Leaf Decoction on Reducing Pain in Post-Partum Mothers at Midwife Nurfitriana's Independent Practice - Abela Mayunita; Nurfitriana (Global Writing Academica Researching and Publishing, 2023)
The purpose of this study was to determine the effectiveness of papaya leaf boiled water in reducing pain in post-partum mothers in the work area of PTMB Nurfitriana. Research Methods: This study used a quasi-experimental with purposive sampling with a sample of 32 people. Data techniques included in Uivariate analysis using frequency distribution and bivariate analysis using calculations. The results of this study found that respondents in the control group and the intervention group in the experimental group after being given papaya leaf boiled water, that most of the post-partum mothers experienced no pain as many as 6 people, 8 people experienced mild pain levels and 2 people experienced moderate pain levels. There was a decrease in pain in the intervention group so that it proved the effectiveness of giving papaya leaf boiled water to pain levels in postpartum mothers at TPMB Nurfitriana.